Pendekatan Sistem dan Kontingensi Manajemen dalam Perspektif Islam - Taufiq, Muhammad; Hariyadi, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the integration of the Systems Approach and the Contingency Approach in educational management from an Islamic perspective, in order to develop an effective management framework that is in line with Sharia objectives. The research uses a descriptive qualitative approach through a literature review of management literature, Islamic education, and relevant conceptual sources. The data is analysed thematically by examining the main concepts of both management approaches and relating them to Islamic values, such as tauhid, syura, amanah, and maslahah. The results of the study show that the integration of the Systems and Contingency Approaches based on Islamic values produces a holistic management model that is adaptive to change without losing its spiritual orientation. This model not only emphasises organisational efficiency and effectiveness but also blessings, social justice, and moral responsibility, making it relevant for application in the management of Islamic educational institutions amid the dynamics of the modern environment